Notes on some crinoid associated decapod crustaceans (Crustacea: Decapoda) of Lakshadweep Archipelago, Central Indian Ocean - Prakash, S.; Marimuthu, N. (Zootaxa, 2020)
Decapod crustaceans symbiotic with echinoderms (sea stars, brittle stars, feather stars, basket stars, sea cucumbers, and sea urchins) possess remarkable diversification in the Indo-Pacific. In the present study, seven species of decapod crustaceans symbiotic with crinoids are recorded based on collections from selected Islands (Agatti, Amini, Bangaram, Kavaratti, Kalpeni, and Minicoy) of Lakshadweep Archipelago. Of these decapods, five caridean shrimps (Alpheidae: Synalpheus carinatus (de Man, 1888), S. comatularum (Haswell, 1882), S. stimpsonii (de Man, 1888); Palaemonidae: Palaemonella pottsi (Borradaile, 1915), Pontoniopsis comanthi (Borradaile, 1915), one brachyuran crab [Pilumnidae: Permanotus purpureus (Gordon, 1934)] and one squat lobster [Galatheidae: Allogalathea elegans (Adams & White, 1848)] were identified. The caridean shrimps have associated with the crinoids Comaster multifidus (Müller, 1841), Phanogenia gracilis (Hartlaub, 1893), P. distincta (Carpenter, 1888), P. multibrachiata (Carpenter, 1888) and Stephanometra indica (Smith, 1876). The brachyuran crab was observed in association with the crinoid Phanogenia gracilis whereas the squat lobsters were associated with Stephanometra tenuipinna (Hartlaub, 1890) and S. indica. Except S. stimpsonii and P. purpureus, all other species were recorded for the first time from India. Here, we provide details on morphology, distribution, habitat, and hosts for all species. We recommend further exploration of the sub-shallow coral reef areas of Lakshadweep as there will be many species that certainly remain to be discovered.